2017
DOI: 10.3390/s17020286
|View full text |Cite
|
Sign up to set email alerts
|

Real Time Apnoea Monitoring of Children Using the Microsoft Kinect Sensor: A Pilot Study

Abstract: Abstract:The objective of this study was to design a non-invasive system for the observation of respiratory rates and detection of apnoea using analysis of real time image sequences captured in any given sleep position and under any light conditions (even in dark environments). A Microsoft Kinect sensor was used to visualize the variations in the thorax and abdomen from the respiratory rhythm. These variations were magnified, analyzed and detected at a distance of 2.5 m from the subject. A modified motion magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 57 publications
1
68
0
1
Order By: Relevance
“…During the tests, which lasted only 40 s per acquisition, the subjects were asked to maintain 'regular respiratory activity'. In a study of young children (between 1 and 5 years) Al-Naji et al [19] found excellent agreement between depth-sensing RR and a piezo-belt reference with correlation coefficients ranging from 0.97 to 0.99 depending on whether bed sheets were used and the background lighting levels. The study was, however, limited to five healthy volunteers in relatively benign conditions.…”
mentioning
confidence: 99%
“…During the tests, which lasted only 40 s per acquisition, the subjects were asked to maintain 'regular respiratory activity'. In a study of young children (between 1 and 5 years) Al-Naji et al [19] found excellent agreement between depth-sensing RR and a piezo-belt reference with correlation coefficients ranging from 0.97 to 0.99 depending on whether bed sheets were used and the background lighting levels. The study was, however, limited to five healthy volunteers in relatively benign conditions.…”
mentioning
confidence: 99%
“…They have only considered a single vital sign, i.e., RR and a single infant, which limits the real applicability of the system. In [63], a contactless real time monitoring system was introduced for measuring respiratory rates and detecting apnoea by exploiting a Microsoft Kinect v2 sensor, as presented in Figure 3c, from the movement of thorax and abdomen in different sleeping positions and various conditions of light including dark environments. They used an improved motion magnification scheme based on the Lanczos resampling method, wavelet pyramid decomposition, temporal band pass filtering and image denoising to magnify the input signal.…”
Section: Motion Based Methodsmentioning
confidence: 99%
“…Camera based children monitoring in hospital environments is given in Al-Naji et al (2017). It measures respiration rates and detects apnoea based on Kinect camera.…”
Section: Other Related Applicationsmentioning
confidence: 99%